Epidemiologia e caracterização genética da resistência aos beta-lactâmicos em enterobactérias não susceptíveis aos carbapenêmicos - Borghi, Mirla (2017)
The resistance to beta-lactams in Enterobacteriaceae is an important public health problem. The carbapenemase production can be highlighted due to its great potential for worldwide dissemination. This study aims to determine the antimicrobial resistance profile, to detect beta-lactam resistance genes and to analyze the genetic polymorphism of carbapenems non-susceptible Enterobacteriaceae isolated from several clinical specimens obtained from patients of hospitals at Grande Vitória. The agar diffusion and gradient tests were used to evaluate the susceptibility profile and to determine the minimum inhibitory concentration. PCR technique was performed for detection of the genes that confer resistance to beta-lactams and the genetic polymorphism was analyzed by PFGE and MLST techniques. The species included in this study were: Klebsiella pneumoniae (n=47), Serratia marcescens (n=14), Enterobacter cloacae (n=4), Enterobacter gergoviae (n=1) e Citrobacter freundii (n=1). These isolates were provided by the Laboratório Central do Espírito Santo (LACEN) and presented resistance to at least one carbapenem. The isolates presented a multiresistance profile against the 25 antimicrobials tested. All isolates carried the blaKPC and the association between the carbapenemase genes and the ESBL genes was observed in all of them. The most prevalent resistance genetic profile (34%) comprised of the genes blaKPC, blaTEM, blaSHV, blaOXA-1 e blaCTX-Mgp1. The PFGE analysis showed the prevalence of two pulsotypes in K. pneumoniae isolates: kpA (40.42%) e kpB (19.14%). The pulsotype smA was found in 13 of 14 S. marcescens isolates. The four E. cloacae isolates showed different pulsotypes. MLST technique was performed in 14 isolates of K. pneumoniae and ST437 and ST340 were the most prevalent. ST437 was identified on the majority (6/7) of isolates from the kpB pulsotype and ST340 was found on all isolates from pulsotype kpA (3/3). ST628, ST37 and ST394 were identified in the pulsotypes kpD, kpO and kpH, respectively. ST628 and ST394 were described for the first time in Brazil.